Rekomendasi Pemilihan Produk Pupuk untuk Budidaya Bawang Merah dengan Kombinasi Metode AHP dan Smart - Victor Alesyus Erlanda (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Red onion farmers in Wonorejo Village, Situbondo Regency, face productivity issues due to the suboptimal selection of fertilizers, which is often based solely on personal experience without clear technical considerations. This situation poses the risk of reduced production yields and even crop failure for farmers. Therefore, this study aims to analyze the ranking of the best fertilizer products suitable for optimizing crop yields using a combination of the Analytical Hierarchy Process (AHP) and Simple Multi-Attribute Rating Technique (SMART) methods. The AHP method was employed to determine the weights of the criteria, while SMART was utilized to assess fertilizer product alternatives based on questionnaire data from five competent farmers. The results show that the criterion, namely fertilizer content ( ), has the most significant influence, with a weight of 0.569368, followed by the criterion, namely soil pH ( ), with a weight of 0.189547, and a Consistency Ratio (CR) value of 0.0775. Based on the final AHP-SMART combination calculation, the ranking results show that the NPK Mutiara Grower ( ) fertilizer alternative ranks first as the best alternative with a value of 0.890262. The following rankings, in order, are NPK 16.16.16 Pak Tani (0.769811), NPK YaraMila (0.582145), KCL Mahkota (0.403442), and Urea (0.102660). In conclusion, NPK Mutiara Grower is highly recommended for farmers.
Reupload File Repository 22 Juni 2026_Yudi Finalisasi Repo 23 Juni 2026_Yudi
Keywords: Decision making; AHP; SMART; Product selection